Identification of Source Contributions to Air Pollution in Penang Using Factor Analysis - Jamil, Mohd Shahiran; Mohamad Japeri, Ahmad Zia Ul-Saufie; Abu Bakar, Amalina Amirah; Muhammad Ali, Khairul Ammar; Ahmat, Hasfazilah (International Journal of Integrated Engineering, 2019)
Penang is one of the rapidly developed states in Malaysia with large numbers of population industrial activities, motor vehicles density and development projects. The concentrations of air pollution parameters in Penang were investigated and analyzed together with meteorological parameters in order to determine their characteristics and contributions to air pollution in Penang using factor analysis (FA). The air pollution parameters include ground level ozone (O3), carbon monoxide (CO), nitrogen dioxide (NO2), sulphur dioxide (SO2) and particulate matters of less than 10 microns in size (PM10) while the meteorological parameters include relative humidity, wind speed and temperature. The data was obtained from the Department of Environment (DOE) for the Universiti Sains Malaysia (USM) monitoring station for the period of 10 years from 2004 to 2013. In this study, concentrations of PM10 was found to be the highest among the air pollutants and the concentrations was at its highest between the months of June to September for almost all years of observation due to the southwest monsoon. As for the source contributions of air pollutions, O3 and meteorological parameters were found to be the largest contributor to air pollutions in Penang, followed by the traffic emissions and industrial activities.